Effective Governance in Managing Change—Common Perspective from Two LensesPositive Organizational Scholarship: Foundations of a New Discipline, edited by CameronKim S., DuttonJane E., and QuinnRobert E.. San Francisco: Berrett-Koehler, 2003.Redefining the Corporation: Stakeholder Management and Organizational Wealth, by PostJames E., PrestonLee E., and SachsSybille. Stanford, CA: Stanford University Press, 2002. - Caldwell, Cam (Academy of Management Review, 2004)
The article reviews the books “Positive Organizational Scholarship: Foundations of a New Discipline,” edited by Kim S. Cameron, Jane E. Dutton, and Robert E. Quinn, and “Redefining the Corporation: Stakeholder Management and Organizational Wealth,” by James E. Post, Lee E. Preston, and Sybille Sachs.